Intermolecular Interaction of Carboxylic Group with Calcium Ions and Dissolution of Solid Scales in Bmim-PF6 and Tba-NfO Ionic Liquid Solution - Muhamad Hadi, Sulaiman; Fatmawati, Adam; Zulkefli, Yaacob; Mohamad Zulhelmy, Sujak; Zulhaizan, Mohd Noor (Universiti Putra Malaysia, 2020)
Understanding the mechanism of solid scale dissolution at a molecular level is important to formulate a new chemical dissolver. A molecular dynamics simulation between glutamic acid diacetic acid (GLDA) with calcite was performed to understand the intermolecular interaction between the carboxylic groups with calcium ions (Ca) during the dissolution process at 90 °C. Two solid scales obtained from oil wells were characterised using a scanning electron microscope (SEM) and energy dispersing x-ray (EDX). The dissolutions test of the solid scales were conducted using two ionic liquids solutions; 1-butyl-3-methylimidazolium hexafluorophosphate (Bmim-PF6) and tetrabutylammonium nonafluorobutane sulfonate (Tba-NfO) to evaluate the ionic liquids for solid scales dissolution. Hydroxyls (-OH) in the carboxylic groups of GLDA have strong intermolecular interactions with Ca that plays a role in the chelation process. Two of the carboxylic groups close to amine have the strongest interactions with calcium ions in calcite. Characterisations result shows that the two solid scales are silica-based and barite based. Barite scales have kink-terrace-step crystal surface. Dissolutions test shows that both ionic liquids solutions can dissolve the silica solid scale up to 2700 ppm.